2015
DOI: 10.3802/jgo.2015.26.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and metachronous malignancy in endometrial cancer patients treated in a tertiary care center of Thailand

Abstract: ObjectiveTo evaluate the prevalence and features of non-endometrial cancers in Thai endometrial cancer (EC) patients.MethodsEC patients treated in our institution were identified and the following data were collected: age, EC stage, histopathology, adjuvant therapy, other cancers, living status, and cause of death.ResultsThe mean age of the 344 patients was 56.8±10.8 years. Fifty (14.5%) had other synchronous and metachronous cancers. Mean ages of the patients with or without other cancers were not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Clinical data of other synchronous or metachronous cancer(s) in some patients were detailed in our previous work. 12 Among the pathologic features studied, early stages and absence of lymph node metastasis were significantly associated with higher rates of MMRd than the comparative groups. Although we found that EMC originated from lower uterine segment (LUS) and endometrioid cancer had higher rate of MMRd, the differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Clinical data of other synchronous or metachronous cancer(s) in some patients were detailed in our previous work. 12 Among the pathologic features studied, early stages and absence of lymph node metastasis were significantly associated with higher rates of MMRd than the comparative groups. Although we found that EMC originated from lower uterine segment (LUS) and endometrioid cancer had higher rate of MMRd, the differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 87%
“…Clinical data of other synchronous or metachronous cancer(s) in some patients were detailed in our previous work. 12…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the presence of synchronous endometrioid EC does not influence the prognosis of patients with stage I OC, even in the presence of deep myometrial invasion [11]. Other authors have found that the OS rate of EC patients who had other cancers was worse than that of patients without other cancers but that disease-specific survival was not significantly different [12]. Based on these data, an appropriate prognosis could be assured within this clinical context.…”
Section: Discussionmentioning
confidence: 97%
“…This was likely because the early detection of cervical cancer is increasing and the number of patients in the metachronous group was relatively higher than that in the synchronous group. The diagnostic interval between primary cancers of different origins of metachronous malignancy has been found to be 3–10 years [ 21 , 24 , 25 ]. The second cancer was diagnosed an average of 5 years after the diagnosis of primary gynecologic cancer in this study.…”
Section: Discussionmentioning
confidence: 99%